Effect of N, K and S on the Yield and Storability of Transplanted Onion (Allium cepa L.) in the Hilly Region - Mozumder, SN; Moniruzzaman, M; Halim, GMA (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> An experiment was conducted during October 2003 to February 2005 at the Agricultural Research Station, Raikhali, Rangamati to investigate the effect of N, K and S on the yield and storability of transplanted onion (Allium cepa L.) in the hilly region. Fourteen combinations of treatments comprising N (0, 100, 125, 150 and 175 kg/ha.), K2O (0, 75, 100, 125, 150 and 175 kg/ha.) and S (0, 12, 24 and 36 kg/ha.) with a common dose of decomposed cowdung @ 10 t/ha and 75 kg P2O5 were used. Application N, K and S significantly increased yield and yield attributes. The maximum plant height (41.8cm), length of bulb (4.49cm) and diameter of bulb (3.85cm), single bulb weight (41.4g/ha), fresh yield (10.33 t/ha) and gross return (Tk.1,23,960/ha) were obtained with the treatment N125K175S24 kg/ha. The maximum number of leaves (7.67/plant) were obtained from N175K100S24, net return (Tk. 91,322/ha) from N125K150S24 and benefit cost ratio (3.89) was obtained from the treatment N150K100S24 kg/ha. Excessive nitrogen caused rapid deterioration and weight loss of bulbs during storage at ambient temperature. Key words: Onion, seedling, storability, hilly region. DOI = 10.3329/jard.v5i1.1459 J Agric Rural Dev 5(1&2), 58-63, June 2007